DATA ANYLYTICS AND VISUALIZATION FOR IOT DATA - Bhat, Neeraj; Chaturvedi, Poonam; Goyal, Vanshika; Bansal, Vrinda (International Journal of Psychosocial Rehabilitation, 2020)
domain names, including healthcare, manufacturing, clever cities, and agriculture. As IoT structures preserve to proliferate, the extent and complexity of statistics generated require sturdy information analytics and visualization strategies to extract treasured insights. This research paper explores the significance of information analytic s and visualization within the context of IoT, discusses the demanding situations, and gives key methodologies and tools for superior choice-making.